2000
DOI: 10.1089/thy.2000.10.243
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Follow-up in Early-Treated Congenital Hypothyroidism: A Problem-Oriented Approach

Abstract: Screening programs for congenital hypothyroidism (CH) dramatically improved the neuropsychological prognosis in affected children. However, mild impairments in cognitive performances, poorer motor skills, defective language abilities, and learning problems have been reported in some studies of early-treated CH children. The occurrence of these defects makes neuropsychological follow-up mandatory. The aim of the present study was to identify those neuropsychological functions that are more frequently affected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 19 publications
2
54
1
7
Order By: Relevance
“…The results showed from the three Speechlanguage Pathology fields investigated, language was the one with higher number of published papers [16][17][18][19][20][21][22][23][24][25][26] . This allows the arguing about this topic in CH children to be more clear and consistent, but do not exclude the importance of other communication aspects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed from the three Speechlanguage Pathology fields investigated, language was the one with higher number of published papers [16][17][18][19][20][21][22][23][24][25][26] . This allows the arguing about this topic in CH children to be more clear and consistent, but do not exclude the importance of other communication aspects.…”
Section: Methodsmentioning
confidence: 99%
“…Subtitles: SG= study group; CG = control group Figure 2 -Contents of localized papers about speech-language disturbances related to congenital hypothyroidism significant delay in language development [17][18][19][20][22][23][24]26 .…”
Section: Michelsson Et Al;1976 25mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the remaining 104 patients who came to our paediatric centre for clinical and hormonal follow-up during 2005-2006, 84 were enrolled in the study. The inclusion criteria at the moment of the testing and filling in the questionnaires were as follows: written consent to the study by the parents and/or the patients, good compliance and adequacy of the levothyroxine (L-T 4 ) treatment assayed by regular evaluations of TSH and FT 4 and intelligence quotient (IQ) in the normal range (low average 80-89; average 90-109; high average 110-119; 4 patients with IQ !80 and 7 with IQ O119 were excluded).…”
Section: Subjectsmentioning
confidence: 99%
“…However, previous studies have indicated that children who receive early treatment for CH have a normal intelligence quotient combined with attention problems (2,3), motor deficits and defects in visuospatial skills, language and memory (4,5). Several studies have correlated these problems with the severity of CH and others with the timing in starting treatment (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%